Teaching Sustainable Business Ethics by Literary Analysis - Novita Dewi; Francisca Reni Retno Anggraini; Fransiscus Asisi Joko Siswanto (Makassar State University, 2020)
Fostering ecological awareness in studying economics is important, bearing in mind that business today is to maintain the sustainability of the earth’s resources. This study examines Heinrich Böll’s “The Balek Scales” and Tayeb Salih’s “A Handful of Dates” to see whether the two short stories are suitable for teaching business and environmental ethics to both students of English and economics. Using content analysis method, this library research uses principles in sustainable business ethics to interpret the two stories. Data analysis shows that both stories exemplify concepts such as autonomy, integrity, justice, professionalism, and environmental awareness. This study concludes that the short stories discussed provide pedagogical tools to teach the basic concepts of professional and environmental ethics in the business world all students today need to know.